2010
DOI: 10.1007/s11270-010-0601-z
|View full text |Cite
|
Sign up to set email alerts
|

Heat Flux Measurements and Modeling of Malodorous Compounds above an Anaerobic Swine Lagoon

Abstract: The concentration of p-cresol and p-ethylphenol, two malodorants typical of swine waste, were measured at 0.5 and 1.5 m above a waste treatment lagoon during two separate campaigns encompassing late winter through early spring and late spring through early summer. Concomitant collection of air temperatures, humidities, insolation, and wind speeds, as well as water column temperatures were done so that heat fluxes could be computed using an energy budget method and Bowen ratio estimates. The empirical model tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Although seasonal temperature ranges may differ from those reported for lagoons in other regions of the USA, the seasonal pattern reported in the present study is similar to those reported for swine lagoons in Iowa (Merrill and Halverson, 2002), Kansas (DeSutter and Ham, 2005), Kentucky (Cook et al, 2010), and North Carolina (Vanotti and Szogi, 2008). Correlations between air and lagoon temperatures and emissions of ammonia, greenhouse gasses, and malodorants have been widely studied, and it is generally agreed that lagoon water temperature is a significant factor in volatilization processes (Harper et al, 2000;DeSutter and Ham, 2005;Aneja et al, 2008;Blunden and Aneja, 2008;Blanes-Vidal et al, 2010;Loughrin et al, 2011). Correlations observed in the present study are described in 3.2.2., 3.2.3., 3.2.5., and 3.3.1.…”
Section: Environmental Factorssupporting
confidence: 86%
“…Although seasonal temperature ranges may differ from those reported for lagoons in other regions of the USA, the seasonal pattern reported in the present study is similar to those reported for swine lagoons in Iowa (Merrill and Halverson, 2002), Kansas (DeSutter and Ham, 2005), Kentucky (Cook et al, 2010), and North Carolina (Vanotti and Szogi, 2008). Correlations between air and lagoon temperatures and emissions of ammonia, greenhouse gasses, and malodorants have been widely studied, and it is generally agreed that lagoon water temperature is a significant factor in volatilization processes (Harper et al, 2000;DeSutter and Ham, 2005;Aneja et al, 2008;Blunden and Aneja, 2008;Blanes-Vidal et al, 2010;Loughrin et al, 2011). Correlations observed in the present study are described in 3.2.2., 3.2.3., 3.2.5., and 3.3.1.…”
Section: Environmental Factorssupporting
confidence: 86%
“…In this research effort we used the Stannard (1997) criteria. These criteria were also successfully applied by the authors for similar studies (Loughrin et al, 2011(Loughrin et al, , 2012Quintanar et al, 2009).…”
Section: Experimental Set Upmentioning
confidence: 99%
“…The Penman method (1948) is one of the most reliable, stable, and costeffective approach to estimate latent energy flux or evaporation from variety of surfaces. This has led to widespread adoption of original or slightly modified version of this method for various applications that require evaporation estimation (e. g., Krishnan and Kushwaha, 1971;Shnitnikov, 1974;Doorenbos and Pruitt, 1977;Cohen et al, 2002;Mahmood and Hubbard, 2002, 2005Wohlfahrt et al, 2009;Quintanar et al, 2009;Loughrin et al, 2011Loughrin et al, , 2012.…”
mentioning
confidence: 99%
See 2 more Smart Citations